BIODEGRADATION OF CHLORPYRIFOS BY A MARINE BACTERIUM Bacillus firmus Strain BY6 ASSOCIATED WITH BRANCHING CORAL Acropora sp. - Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2007)
A bacterium which utilizes chlorpyrifos as a sole source of carbon and energy was isolated from coral surface. The organism utilized chlorpyrifos up to 25 mg l-1. The lag phase and time for degradation, however, were severely prolonged at chlorpyrifos concentrations above 10 mg l-1 . The growth of kinetics of coral bacterium was studied in batch culture. Estimation of maximum growth rates (μmax), obtained from turbidity measurements, was 0.14 h-1 and half-saturation growth constant (Cs) was 9.34 mg l-1 chlorpyrifos. This strain demonstrated greatest similarity to members of the order Bacillales and was closest to members of the Bacillus firmus group.